Calculation and benchmark of fluence-to-local skin equivalent dose coefficients for neutrons with FLUKA, MCNP, and GEANT4 Monte-Carlo codes. (19th August 2021) - Frosio, Thomas; Bertreix, Philippe; Menaa, Nabil; Thomas, Samuel
Abstract: Dose equivalent limits for single organs are recommended by the ICRP (International Commission for the Radiological Protection publication 103). These limits do not lend themselves to be measured. They are assessed by convoluting conversion factors with particle fluences. The Fluence-to-Dose conversion factors are tabulated in the ICRP literature. They allow assessing the organ dose of interest using numerical simulations. In particular, the literature lacks the knowledge of local skin equivalent dose (LSD) coefficients for neutrons. In this article, we compute such values for neutron energies ranging from 1 meV to 15 MeV. We use FLUKA, MCNP and GEANT4 Radiation transport Monte-Carlo simulation codes to perform the calculations. A comparison between these three codes is performed. These calculated values are important for radiation protection studies and radiotherapy applications.